Genome-wide meta-analysis of muscle weakness identifies 15 susceptibility loci in older men and women - Jones, Garan; Trajanoska, Katerina; Santanasto, Adam J.; Stringa, Najada; Kuo, Chia-Ling; Atkins, Janice L.; Lewis, Joshua R.; Duong, ThuyVy; Hong, Shengjun; Biggs, Mary L.; Luan, Jian’an; Sarnowski, Chloe; et al. (Nature communications, 2021)
Low muscle strength is an important heritable indicator of poor health linked to morbidity and mortality in older people. In a genome-wide association study meta-analysis of 256,523 Europeans aged 60 years and over from 22 cohorts we identify 15 loci associated with muscle weakness (European Working Group on Sarcopenia in Older People definition: n = 48,596 cases, 18.9% of total), including 12 loci not implicated in previous analyses of continuous measures of grip strength. Loci include genes reportedly involved in autoimmune disease ( HLA-DQA1 p = 4 × 10 −17 ), arthritis ( GDF5 p = 4 × 10 −13 ), cell cycle control and cancer protection, regulation of transcription, and others involved in the development and maintenance of the musculoskeletal system. Using Mendelian randomization we report possible overlapping causal pathways, including diabetes susceptibility, haematological parameters, and the immune system. We conclude that muscle weakness in older adults has distinct mechanisms from continuous strength, including several pathways considered to be hallmarks of ageing. Muscle weakness has been associated with morbidity and mortality in older people. Here, the authors have investigated this trait further by performing a genome-wide meta-analysis of grip strength and Mendelian randomization to discover causal relationships between muscle weakness and other diseases.